My Peerless story : it starts with the collar - Segal, Alvin Cramer, 1933- (Footprints (Cheltenham, England), 2017)
"In 1951, Alvin Cramer Segal, at the age of eighteen and without a formal education, started working in the factory of his stepfather's company in Montreal. Today he is the chairman and chief executive officer of the largest supplier of men's fine-tailored clothing in North America, and is considered an outstanding business and community leader, at the forefront of policy-making in Canada's apparel industry, with commitments to philanthropic efforts that echo his business accomplishments. In My Peerless Story, Segal recounts how he learned business from the collar down and from the ground up, transforming a family-owned business into one that would eventually come to license labels such as Ralph Lauren, Calvin Klein, and Michael Kors. Sharing anecdotes and personal experiences, Segal describes the history of garment manufacturing in Montreal and his intuitive strategies to leverage growth by improving fabrics, and adapting to innovative changes in the industry, eventually becoming the main inventory source of designer label suits to major department stores. Written from the heart, not a as handbook but rather as the story of a well-suited business career, My Peerless Story nonetheless includes relevant business lessons for the aspiring and inspired."--